ANALISIS KEBIJAKAN PEMERINTAH DAN PARTISIPASI MASYARAKAT DALAM UPAYA PENANGGULANGAN ROB (Studi Kasus Kota Tegal) - Ardiansyah, Soni Hazam; Santosa, Edi; Widayati, Wiwik (Journal of Politic and Government Studies, 2013)
Topographically, Tegal city located in low-lying areas in the northern coastal areas of Java Sea. This topographic conditions that led to the city of Tegal has the potential vulnerability of disaster caused by sea water is quite high. The city is faced with the question every year tidal flood. According to Law No. 32 of 2009 in the protection and management of environmental, district / city government duty and authority to determine level of district / city. Tegals city government has a duty to establish appropriate policies in order to rob the response. Development paradigm has gradually shifted its efforts on increasing public participation in various phases of development activities. Principles of the implementation of the program is to put the public other than as objects of development is also a subject or perpetrator of development that is expected to continue / expand the development program and can solve their own problems, especially in improving the quality of settlement environment. Of it is to know how public participation in the prevention rob tegal city.In this study the researchers used a combination of qualitative and quantitative methods (mixed methods design). Mixed methods design is a procedure to collect data, analyze and "mixing" both qualitative and quantitative methods in a single research study to understand the problem. This research will use models aim sampling (purposive sampling). Understanding of purposive sampling is carefully selected samples were deemed worthy or representatatif in providing information on research problems.Implementation strategies used by the Government in response to rob Tegal is by involving all relevant agencies and elements rob problem, namely by engaging on education, the local, non-governmental organizations, communities and society tokok affected rob. The involvement of all elements and elements that comprise the city of Tegal; stages of planning, organizing, implementation and evaluation. Prior to the establishment of management policies rob, to the community, especially people who were targeted socialized programs in advance of planned steps to be performed Tegal City Government to the areas affected by flooding, in addition to the community in hopes to have a comprehensive knowledge and understanding, as well can actively participate in the later stages implmentasi.In general, the respondents' participation in the management process is classified as long rob upper middle. Community actively participate in the planning, establishment and implementation of government policies by Rob Tegal. It is also due to the efforts of community engagement undertaken by the City of Tegal.Keywords: Policy Analysis , Public Participation